Lessons from Italian Monetary Unification - James Foreman-Peck (Cardiff University, Cardiff Business School, 2005)
This paper examines whether the states brought together in the Italian monetary union of the nineteenth century constituted an optimum monetary area, either before or after unification. Interest rate shocks indicate close relations between states in northern Italy but negative correlations between the North and the South before unification, suggesting some advantages of continued Southern monetary independence. The proportion of Southern Italian trade with the North was small, in contrast to intra- Northern trade, and therefore monetary independence imposed a light burden. Changes in the wheat market indicate that the South and North after unification (though not probably because of it) increasingly specialised according to their comparative advantages. Coupled with differences in economic behaviour of the Southern economy, this meant that monetary policies appropriate for the North were less so for the South. In the face of agricultural shocks originating in the New World and in France, the South would have gained from depreciating its exchange rate against the North or against the non-Italian world. As it was, nineteenth century Italian monetary union did not create the conditions for its own success, contrary to the findings of Frankel and Rose (1998) for the later twentieth century.
Keywords: E42; N23; F15; F33; 330